Child-Friendly City: Failure to Build Collaboration - Nila Wahyuni; Rahmadhona Fitri Helmi; Hidayatul Fajri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
Collaborative governance has received massive public administration attention by scholars and practitioners in the last decade as a theory and practice. Even so, in its application, collaboration often fails due to the inability of stakeholders to build mutual understanding. This study aims to describe and analyze the causes of failure of stakeholders at the Collaboration Forum in creating a mutual understanding of the Child-Friendly City of Padang City. This research uses the descriptive qualitative method. The data were collected by interviews, field observations, and document review. Interviews were conducted individually and semi-structured with state and non-state stakeholders. The results showed that the collaboration forum did not work effectively because of the failure of stakeholders to integrate into building mutual understanding caused by sectoral egos, lack of mutual understanding between stakeholders, and lack of involvement of non-state stakeholders.